KENDALA PENERAPAN PEMBELAJARAN TEMATIK DI KELAS RENDAH SEKOLAH DASAR - Sukiniarti Sukiniarti (Perspektif Ilmu Pendidikan, 2014)
Based on the curriculum of the unit level of education or school-based curriculum (KTSP), the thematic earning is designed to be implemented at the lower grades of primary school, namely grade 1, 2, and 3. However, in the Curriculum of 2013 the thematic learning is designed to be applied at all grades from 1st grade to the 6th grade, and even at the higher school levels. The purpose of this study was to describe the constraints faced by the lower grade elementary school teachers in developing the lesson plans, selecting the media, and deciding on the use of the appropriate thematic learning methods. Moreover, this study was to describe the constraints in implementing the thematic learning in the lower grade classrooms. The subjects of this qualitative research were lower grade teachers of elementary school in Bangka Belitung province. The data were collected through questionnaires, interviews, observation, and review of lesson plan documents formulated by the teachers. The results showed, the constraints experienced by the teachers included the difficulty in developing the thematic lesson plan, determining the method, selecting the media, and preparing the evaluation tools. From this study it can be concluded that the application of the thematic learning in lower grades will experience problems if the teachers are not creative and do not have a broad understanding of the selected theme in relation to the subjects combined.